The Effectiveness of Using Teaching Strategies in Teaching Vocabulary to Primary School Students in Benghazi - Elarafi, Nora; Agsebat, Halah (Scientific Journal of University of Benghazi, 2022)
The present study is mainly concerned with teaching vocabulary to fourth-year primary school students through two language teaching approaches. The study compares modern teaching strategies with traditional ways of pedagogy in teaching vocabulary. The strategies used in this study include classroom strategies, cooperative learning, inquiry-based instruction and visualization. The sample of this study consisted of thirty beginner students at Ibn Sina Primary School in Benghazi. The sample was divided into two groups (an experimental group and a control group), each consisting of fifteen students. The data were analyzed using the statistical program SPSS. Before implementing the strategies, a pre-test was given to the participants while the post-test was used immediately after the treatment. The analysis of the collected data revealed that the students in the experimental group achieved better results than the control group. Yet, the post-test students achieved better results than the pre-test in the experimental group. Both of the experimental tests (pretest and post-test) achieved higher results than the results of the students in the control group.